Enhancing inclusion in the national digital literacy index: From measurement to empowerment - Natasya Zahra (Center for Indonesian Policy Studies (CIPS), 2023)
The Directorate General of Informatics Application (DGIA) of the Indonesian Ministry of Communication and Informatics (MOCI) has developed a digital literacy index to assess the state of national digital literacy, map the digital competencies of Indonesians, and develop a framework for measuring digital literacy across Indonesia's 34 provinces. This will assist the DGIA in achieving its objective of providing digital literacy training to 50 million Indonesians by 2024. The index uses a self-assessment tool to measure key digital literacy competencies, such as the knowledge and ability to operate digital tools. However, this assessment method suffers from technical and operational inaccuracy. Consequently, the DGIA cannot identify the specific skill sets that Indonesians struggle with or the segments of society that require greater digital literacy support. This hinders the development of an effective and targeted digital literacy training program.
Keywords: 330